ENDOSCOPIC DIAGNOSTICS AND TREATMENT OF INTRABILIARY RUPTURE OF LIVER HYDATID CYST - S.SH. MUSOEV; SH.SH. AMONOV 1,2; Z.SH. FAYZIEV; M.O. OLIMI (Avicenna Tajik State Medical University, 2023)
Hepatic echinococcosis (HE), also known as hydatid disease in humans, is a parasitic disease prevalent in countries with a developed animal husbandry industry. The parasite mainly impacts the liver and lungs of an individual and presents itself as a cyst. Severe complications of HE are suppuration, communicating rupture of hepatic hydatid cysts (HHC) into the abdominal or pleural (through the diaphragm) cavities, adjacent hollow organs, and bile ducts. In the latter case, the ducts are blocked by HHC elements with the development of obstructive jaundice (OJ). The article presents a rare clinical case of successful treatment of a patient with HHC, complicated by a communicating rupture of hepatic hydatid cysts into the biliary tract and the development of OJ. The patient underwent endoscopic retrograde cholangiopancreatography (ERCP), endoscopic papillosphincterotomy (EPST), chitin coat extraction, and mechanical block elimination with biliary tract lavage.